A Study Of Differences In Mathematical Reasoning Among Junior High Students With Field Independent And Field Dependent Cognitive Styles - Fujiama Marjud; Aan Hasanah; Lukman Lukman; Putri Ardhanita Harahap (Universitas Wiralodra, 2025)
Mathematical reasoning plays a vital role in helping students understand concepts, identify patterns, and solve problems effectively. This study aimed to investigate whether students with Field-independent (FI) and Field-dependent (FD) cognitive styles exhibit significant differences in their mathematical reasoning abilities. To examine the variation in students’ reasoning skills according to their cognitive styles, a quantitative approach using a comparative method was employed. After a preliminary test of homogeneity of variances using Levene's Test, which produced a significance value of 0.820 (> 0.05), Data were analyzed using an Independent Samples t-test. The results indicated that the assumption of equal variances was met, thereby validating the use of parametric analysis. The t-test revealed a statistically significant difference between the two cognitive style groups, with a t-value of 3.232, 40 degrees of freedom, and a significance level of 0.002 (< 0.05). In terms of mathematical reasoning, students identified as FI performed better than those classified as FD. This finding suggests that while FD learners tend to rely more on external cues and structured guidance when solving problems, FI learners are generally more analytical and able to process information independently. The findings also suggest that pupils' capacity for mathematical reasoning is significantly influenced by their cognitive style. These results emphasise the necessity of varied teaching strategies that take into account both learning styles from a pedagogical standpoint. Teachers can build more inclusive, balanced, and productive mathematics learning environments by incorporating exploratory, Problem-based tasks are more suitable for FI learners, whereas structured instructional approaches better support FD learners.